The Transition from Underpricing Residential Electricity in Bangladesh : Fiscal and Distributional Impacts - Ahmed, Faizuddin; Trimble, Chris; Yoshida, Nobuo (World Bank, Washington, DC, 2014)
The electricity sector in Bangladesh has been facing unprecedented challenges, with severe capacity constraints and sector subsidies that quadrupled from 0.2 percent to 0.8 percent of gross domestic product (GDP) between 2010 and 2012, driving the government's fiscal deficit deeper. This policy note examines the poverty and distribution impact of one such reform-residential electricity tariff increases-along with their fiscal implications. A challenge of such adjustments is how to minimize their impact on the poor and vulnerable. Using household survey data, this report studies the distributional and fiscal implications of the residential tariff adjustments between March 2010 and March 2012 on to inform policy dialogue on the provision and targeting of electricity subsidies. Electricity subsidies are defined as the difference between the cost of supplying a unit of electricity and the tariff the end-user is charged for a given unit. Between 2010 and 2012, real cost of supply increased almost 20 percent. This policy note focuses on just one part of a much broader and complex system of connected energy policies. The policy implications of this analysis should only be considered in light of this broader context. In particular, this note does not study in detail the complex issues of generation and operational efficiency (in transmission and distribution). Second, this note does not study the political economy of tariff and subsidy reform. Tariff increases have been a source of social unrest, and planned increases could generate additional unrest. It will be important for the government to consider the political economy of further reform carefully. Moving forward, both of the new slab systems being discussed could relieve the fiscal burden of subsidies.